Intrinsic and extrinsic motivation among adolescent ten-pin bowlers in Kuala Lumpur, Malaysia - Teo, E.W.; Khoo, S.; Wong, R.; Wee, E.H.; Lim, B.H.; Rengasamy, S.S. (De Gruyter Open, 2015)
Motivation has long been associated with sports engagement. However, to date no research has been performed to understand the domain of motivation among ten-pin bowlers. The purpose of this study was to investigate different types of motivation (i.e., intrinsic vs. extrinsic) based on self-determination theory from the perspective of gender and the bowler type (competitive vs. casual). A total of 240 bowlers (104 male, 136 female; 152 competitive, 88 casual) with a mean age of 16.61 ± 0.78 years were recruited in Kuala Lumpur. The Sport Motivation Scale, a 28-item self-report questionnaire measuring seven subscales (i.e., intrinsic motivation to know, intrinsic motivation to accomplish, intrinsic motivation to experience stimulation, extrinsic motivation to identify regulation, extrinsic motivation for introjection regulation, extrinsic motivation to external regulation, and amotivation) was administered. Results showed significant differences (t=10.43, df=239, p=0.01) between total scores of intrinsic and extrinsic motivation among tenpin bowlers. There were significant gender differences with respect to intrinsic motivation to know, intrinsic motivation to accomplish, intrinsic motivation to experience stimulation, and extrinsic motivation to identify regulation. However, no significant bowler type differences were found for either the intrinsic (t=-1.15, df=238, p=0.25) or extrinsic (t=-0.51, df=238, p=0.61) motivation dimensions. In conclusion, our study demonstrated substantial intrinsic motivation for gender effects, but no bowler type effects among adolescent ten-pin bowlers.